Indwelling pleural catheters for non-malignant effusions: a multicentre review of practice. Issue 10 (16th December 2013) - Bhatnagar, Rahul; Reid, Elaine D; Corcoran, John P; Bagenal, Jessamy D; Pope, Sandra; Clive, Amelia O; Zahan-Evans, Natalie; Froeschle, Peter O; West, Douglas; Rahman, Najib M; Chatterji, Sumit; Sivasothy, Pasupathy R; et al.
Abstract : Indwelling pleural catheters (IPCs) are commonly used in the management of malignant pleural effusion (MPE). There is little data on their use in non-malignant conditions. All IPC insertions for non-malignant cases from five large UK centres were found using prospectively maintained databases. Data were collected on 57 IPC insertions. The commonest indications were hepatic hydrothorax (33%) and inflammatory pleuritis (26%). The mean weekly fluid output was 2.8 L (SD 2.52). 48/57 (84%) patients had no complications. Suspected pleural infection was documented in 2 (3.5%) cases. 33% (19/57) of patients underwent 'spontaneous' pleurodesis at a median time of 71 days. Patients with hepatic disease achieved pleurodesis significantly less often than those with non-hepatic disease (p=0.03). These data support the use of IPCs in select cases of non-malignant disease when maximal medical therapy has failed.